Konsep Kepemimpinan dalam Hadis Nabi dan Relevansinya terhadap Etika Kepemimpinan Berbasis Artificial Intelligence - Layalil Maghfiroh Zain; Nasrulloh (Al-Kindi, 2026)
Development of Artificial Intelligence (AI) in the era of Society 5.0 raises various ethical challenges that require a strong moral foundation, especially for leaders who utilize technology in the decision-making process. This study aims to analyze the concept of leadership in the hadith of the Prophet Muhammad SAW and examine its relevance to AI-based leadership ethics. The method used is a literature study by examining hadiths related to the values of trustworthiness, fairness, siddiq, tabligh, and fathanah, and relating them to contemporary technology ethics and AI ethics literature. The results show that prophetic leadership values not only reflect moral principles in Islam but can also be used as an ethical framework in the development and implementation of AI. The value of trustworthiness is related to accountability and data security; fairness is related to the prevention of algorithmic bias; truthfulness is related to data honesty and information validity; communication is related to algorithm transparency; and wisdom is related to prudence in risk mitigation and technology-based decision making. Thus, this study confirms that the integration of prophetic leadership values in AI ethics can be an effective approach in creating leadership that is fair, responsible, and oriented towards public benefit.